Association of Health Status and Health Behaviors with Weight Satisfaction vs. Body Image Concern: Analysis of 5888 Undergraduates in Egypt, Palestine, and Finland - El Ansari, Walid (Nutrients, 2019)
Little is known about the relationships between weight satisfaction, body image concern, healthy nutrition, health awareness, and physical activity among college students across culturally different countries. We assessed country and sex-specific associations between health status (self-rated health, depression, BMI), healthy behavior (healthy nutrition, physical activity, health awareness), weight satisfaction, and body image concern via a cross-sectional survey (5888 undergraduates) in Egypt, Palestine, and Finland. This health and wellbeing survey employed identical self-administered paper questionnaires administered at several Universities in two Eastern Mediterranean countries (Egypt, Palestine—Gaza Strip), and an online-survey comprising the same questions in Finland. Regression analyses were employed. Health status variables exhibited the strongest associations; high BMI and more depressive symptoms were more often among students satisfied with their weight (except in Palestine), but they were positively associated with body image concern irrespective of country or gender. Self-rated health was not associated with body image concern or weight satisfaction. Healthy behaviors were not associated with body image concern or weight satisfaction. Depressive symptoms and BMI were the most prominent predictors for body image concern. There were country-specific consistent results when using the body image concern score. Further research is necessary to compare body image across different cultures and countries.